2020
DOI: 10.1016/j.biopsych.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Prenatal Stress Is Associated With Altered Uncinate Fasciculus Microstructure in Premature Neonates

Abstract: BACKGROUND: Maternal prenatal stress exposure (PNSE) increases risk for adverse psychiatric and behavioral outcomes in offspring. The biological basis for this elevated risk is poorly understood but may involve alterations to the neurodevelopmental trajectory of white matter tracts within the limbic system, particularly the uncinate fasciculus. Additionally, preterm birth is associated with both impaired white matter development and adverse developmental outcomes. In this study we hypothesized that higher mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 104 publications
1
58
0
3
Order By: Relevance
“…These findings are supported by evidence from fetal stress models demonstrating that full-term and preterm neonates exposed to prenatal stress showed alterations in brain development. More specifically, prenatal stress (e.g., maternal anxiety/depression) was associated with reductions in region-specific gray matter volume [i.e., PFC, temporal lobe (140)], alterations in white matter microstructure (e.g., amygdala, limbic system) (141)(142)(143), and reduced functional and structural connectivity between the amygdala, limbic, and frontal regions in infants (144)(145)(146). The effects of prenatal stress on brain development have been extensively reviewed elsewhere [see (147)(148)(149)].…”
Section: Neonatal Stress and Brain Developmentmentioning
confidence: 99%
“…These findings are supported by evidence from fetal stress models demonstrating that full-term and preterm neonates exposed to prenatal stress showed alterations in brain development. More specifically, prenatal stress (e.g., maternal anxiety/depression) was associated with reductions in region-specific gray matter volume [i.e., PFC, temporal lobe (140)], alterations in white matter microstructure (e.g., amygdala, limbic system) (141)(142)(143), and reduced functional and structural connectivity between the amygdala, limbic, and frontal regions in infants (144)(145)(146). The effects of prenatal stress on brain development have been extensively reviewed elsewhere [see (147)(148)(149)].…”
Section: Neonatal Stress and Brain Developmentmentioning
confidence: 99%
“…Finally, in this study we considered the effect of home environment at 22 months on developmental outcome in CHD. Prenatal as well as postnatal environmental enrichment improves outcome in rats with perinatal hypoxia‐ischemia (Duran‐Carabali et al, 2018; Durán‐Carabali et al, 2019), and we have previously observed altered white matter development in infants born prematurely who experienced prenatal stress exposure (Lautarescu et al, 2019). An improved prenatal environment such as increased maternal exercise or reduced maternal stress may improve brain and cognitive development (Miguel et al, 2019).…”
Section: Discussionmentioning
confidence: 77%
“…Prenatal as well as postnatal environmental enrichment improves outcome in rats with perinatal hypoxia-ischemia (Duran-Carabali et al, 2018;Durán-Carabali et al, 2019), and we T A B L E 3 Regression coefficients predicting cognitive composite score and language composite score in children with CHD. have previously observed altered white matter development in infants born prematurely who experienced prenatal stress exposure (Lautarescu et al, 2019). An improved prenatal environment such as increased maternal exercise or reduced maternal stress may improve brain and cognitive development (Miguel et al, 2019).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Recent studies have investigated the role of both ante- and postnatal parental stress and anxiety in child development and behaviour ( Bendiksen et al, 2020 ; Kvalevaag et al, 2013 ; Polte et al, 2019 ; Rees et al, 2019 ), although inconsistencies between study methodologies and findings make definite conclusions difficult ( Rees et al, 2019 ; Tarabulsy et al, 2014 ). Postnatal maternal stress and anxiety are believed to have significant long-term implications for child brain maturation ( Lautarescu et al, 2020 ; Qiu et al, 2013 ) and behavioural development ( Field, 2018 ), particularly in very preterm infants ( Hadfield et al, 2017 ). Possible mechanisms mediating these associations include reduced maternal sensitivity ( Kertz et al, 2008 ; Nicol-Harper et al, 2007 ), unpredictability of maternal behaviour ( Davis et al, 2017 ), and altered mother-infant attachment ( Hadfield et al, 2017 ; Stevenson-Hinde et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%